Re-positioning faculty development as knowledge mobilization for health professions education - Ng, Stella L. (Perspect Med Educ, 2017)
Faculty development as knowledge mobilization offers a particularly fruitful and novel avenue for exploring the research-practice interface in health professions education. We use this ‘eye opener’ to build off this assertion to envision faculty development as an enterprise that provides a formal, recognized space for the sharing of research and practical knowledge among health professions educators. Faculty development’s knowledge mobilizing strategies and outcomes, which draw upon varied sources of knowledge, make it a potentially effective knowledge mobilization vehicle. First, we explain our choice of the term knowledge mobilization over translation, in an attempt to resist the false dichotomy of ‘knowledge user’ and ‘knowledge creator’. Second, we leverage the documented strengths of faculty development against the documented critiques of knowledge mobilization in the hopes of avoiding some of the pitfalls that have befallen previous attempts at closing knowing-doing gaps. Through faculty development, faculty are indeed educated, in the traditional sense, to acquire new knowledge and skill, but they are also socialized to go on to form the systems and structures of their workplaces, as leaders and workers. Therefore, faculty development can not only mobilize knowledge, but also create knowledge mobilizers. Achieving this vision of faculty development as knowledge mobilization requires an acceptance of multiple sources of knowledge, including practice-based knowledge, and of multiple purposes for education and faculty development, including professional socialization.